Tips for Integrating Land and Wildlife Management: Deer in Forests - William M. Giuliano; John M. Olson; Cailey Thomas (EDIS, 2013)
Prized by hunters and wildlife enthusiasts alike, white-tailed deer are a popular species found throughout Florida. As such, they are often the focus of management for landowners, managers, and lessees who want to improve deer populations while maintaining other land uses such as timber production. This 2-page fact sheet provides some deer habitat improvement tips that focus primarily on raising the quality of deer forage but that also will help you grow better cover by improving plant diversity and productivity. Written by William M. Giuliano, John M. Olson, and Cailey Thomas, and published by the UF Department of Wildlife Ecology and Conservation, January 2013.